In memoriam: Alan Deyermond y la oralidad en la literatura medieval hispánica - Masera Cerutti, Mariana (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2012)
Alan Deyermond’s presence has been essential for Lyra Minima. In this paper I shall focus on three themes that he studies through time: orality, female authorship and the interaction between learned and popular lyric. Transitional text is an essential concept proposed by Deyermond to designate texts generated between oral and written traditions. His studies demonstrates the transitional texts existence in Middle Ages and the beginning of the Renaissance. The oral/written relationship at that time appears as a transformation, as an upgrade and s a symbiosis. For Deyermond, it is probable that traditional lyrics origins were women’s songs, with elemental and symbolic imagery